A content analysis of information technology articles in Library Trends - Cabornay, Imelda D. (2001)
This study sought to determine any trend in the field of librarianship as reflected in the articles of Library Trends. Specifically, it was undertaken to: 1) Find out the different areas in librarianship in which IT is being discussed; in which area/s is IT most/least discussed; 2) Find out at what period of time Library Trends registered the highest/lowest frequency of articles on information technology; 3) Determine the space allocations of theses articles; 4) Determine whether there is an increasing trend of IT articles in librarianship in Library Trends; and 5) Validate the recommendations in Campanano's thesis specifically on collection management. Content analysis was used on the articles of the journal Library Trends to determine the importance given towards the topic of information technology and its contribution to the field of librarianship as a whole.